Emerging threat in antifungal resistance on superficial dermatophyte infection - Sultana, Razia; Wahiduzzaman, Md (Bangladesh Medical Journal Khulna, 2019)
Background: Dermatophytosis are most common fungul infection globally and according to WHO the prevalence is about 20-25% and does not spare people of any race or age. Over the past few years antifungal resistance has been emerged due to irrational use of antifungal drugs in cutaneous mycosis. Objective: The aim of the study is to evaluate the efficacy of different antifungul drugs (Terbinafin. Fluconazole, Itraconazole, Griseofulvin) on superficial mycosis depending on various factors. Methods: This prospective study was conducted among the Superficial fungul infected patients from April' 2017 to October 2017 in Khulna Medical College Hospital (KMCH) and dermatologist's private chamber in Khulna city. All the enrolled patients were put on oral Terbinafin, Fluconazole, Itraconazole and Griseofulvin. Each patient was given single antifungal drug orally. These cases were thus followed up after two months of treatment to look for persistent infection, cure or any relapse clinically. Result: Among 194 patient 89 were given Tab. Terbinafin (250mg) where resistance cases were 20.22%. More cases (33.96%) were resistant to Cap. Fluconazol (50mg). High percentage of cases were resistant to Cap. Itraconazole (76.47%). Griseofulvin resistant cases were observed in 25.71%. Drug response is very poor (69%) in patient who had been suffering from diabetes mellitus. Conclusion: Appropriate antifungal drugs should be chosen with strict indication, dose, duration, selection of perfect local preparation and taking laboratory facilities where necessary. Bang Med J (Khulna) 2018; 51 : 21-24